CAREER DEVELOPMENT - A LIFESPAN PERSPECTIVE - Maria POPOVA-HRISTOVA (Editura Universitatii Transilvania din Brasov, 2019)
Career counseling includes tools that allow us to define at a young age what our strengths and weaknesses are, what field of activity we would feel comfortable about and what we get from a profession. Thanks to such a consultation, we get the opportunity to make an informed career path decision that we do not regret later on. We asked 224 people in Bulgaria how they made their choice for the profession they chose through a survey-students for themselves and parents for their children. We were interested in choosing the specialty to be taught in a higher education institution. We were also interested in being aware of the curriculum of the chosen specialty, and whether they had information about the duties they were expected to perform when they started work in the specialty. We asked them if, in selecting a specialty, they had information on the average pay for the position they would occupy with the subject studied.